Cooperative Learning with Mobile Phones ina ContextofVulnerability:Outcomes for Coexistencein School - Carlos Monge López; Héctor del Castillo Fernández; Mônica de Carvalho Magalhães Kassar (Universidad Autónoma de Baja California, 2022)
This research seeks to describe and understand how an intervention based on cooperative learning and the use of mobile phones in early childhood and elementary classrooms promotes harmonious relations in schools within a context of socioeconomic vulnerability and cultural diversity. A case study was conducted in a Brazilian school (on the Bolivian border), using different qualitative techniques to collect information (participant observation, semi-structured interviews, and a discussion group). The results point to a reduction in disruptive behavior, academic disengagement, and exclusion, attributed primarily to a combination of cooperative factors enhanced by the use of mobile telephones (positive interdependence, a sense of belonging, heterogeneous grouping, individual responsibility, stimulating interaction, group identity, and teamwork skills). In this case, the use of mobile phones in education, coupled with a cooperative methodology, improved school life in the group studied.